Synthesis of Colloidal Gold Nanorods with Plasmon Absorbance Wavelength in the Near Infrared Region. Issue 30 (28th June 2016) - Angelats-Silva, Luis M.; Asmat-Campos, David; León-León, Henry; Wilkinson, Kevin A.; Sánchez-Vaca, Daniel A.; López-Milla, Alcides
ABSTRACT: We report preparation and characterization of colloidal gold nanorods (AuNR) with plasmon absorbance over 950 nm and an aspect ratio of 7.2 by tuning silver nitrate concentration and the CTAB/BDAC ratio during growth. Samples were analyzed by scanning transmission electron microscopy, X-ray diffraction, UV-vis absorption spectroscopy and measurement of zeta potential. Addition of 170 μM silver nitrate to the CTAB-containing reaction mixture allowed preparation of AuNRs with a maximum absorbance peak at 941.8 nm and a yield around 96%. Optimization of the BDAC/CTAB ratio allowed for a further redshift of the absorbance maximum to 954.0 nm, but with poorer yields.